Schoolchildren's habits and knowledge about oral health - Valdirene Miranda Esteves Orsi; Alessandro Aparecido Pereira; Flávia Martão Flório; Luciane Zanin de Souza; Patrícia Boaretto; Poliana Poin Souza Pinheiro; Silvia Milena Cinel Agosteneli (Faculdade São Leopoldo Mandic, 2009)
Objective: The aim of this study was to assess the habits and knowledge of schoolchildren who take part in a preventive educational program developed by "Universidade Federal de Alfenas", Minas Gerais, Brazil. Methods: The sample was composed of 386 boys and girls, regularly enrolled in four public schools in Alfenas, Minas Gerais, Brazil, in which the program has been implemented. The criterion for a schoolchild's participation in the study was having attended the program for four consecutive years. Data were collected through a questionnaire about oral health. Chi-square test, with significance level of 5%, was used to assess whether there were differences concerning the knowledge acquired. Results: As regards caries transmissibility, 39.1% answered that caries is a disease, but that it is not transmitted. Most of the interviewees, 88.6%, use their own toothbrushes to brush their teeth. About the use of dental floss, 41.97% of the interviewees answered that its function is "to remove food remains and bacterial plaque between teeth". When questioned about the usefulness of fluoride use, 53.62% answered that its purpose is "to avoid caries in the teeth". Conclusion: After the analysis of the results, it can be concluded that some points in the program need further emphasis. However, the Oral Health Education Program has met its objective of transmitting knowledge to schoolchildren, who demonstrated a good level of information about oral health.